AFM-in-SEM as a Tool for Comprehensive Sample Surface Analysis. (May 2020) - Novotna, Veronika; Horak, Josef; Konecny, Martin; Hegrova, Veronika; Novotny, Ondrej; Novacek, Zdenek; Neuman, Jan
Abstract: Abstract : Key features and applications of a unique atomic force microscope (AFM), the LiteScope™, which can be integrated into a scanning electron microscope (SEM) is reported. Using the AFM-in-SEM as one tool combines the capabilities of both systems in a very efficient way. The LiteScope design features advanced Correlative Probe and Electron Microscopy (CPEM)™ imaging technology that allows simultaneous acquisition of multiple AFM and SEM signals and their precise in-time correlation into a 3D CPEM view. AFM-in-SEM advantages are presented using several examples of applications and AFM measurement modes including CPEM, material electrical and mechanical properties together with nanoindentation, and focused ion beam (FIB) applications.